IMPLEMENTATION OF COOPERATIVE MODEL TYPE TWO STAY TWO STRAY IN INCREASING SOCIAL STUDIES LEARNING 5TH GRADER STUDENT STATE ELEMENTARY SCHOOL 3 KRAKAL 2013/2014 ACADEMIC YEAR - Ihsan, Ahmad Nur (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Implementation of Cooperative Model Type Two Stay Two Stray in Increasing Social Studies Learning 5th Grader Student State Elementary School 3 Krakal 2013/2014 Academic Year. The purpose of this research to describe the implementation of cooperative model Two Stay Two Stray in increasing Social Studies learning and found the problem with a solution. This research used Classroom Action Research technique and implemented in three cycles. The results showed that: Implementation model of cooperative two stay two stray can improve Social Studies Learning 5th Grader Student. Problems were: smart students more active and dominating, the seating arrangement is less. The solution are: to motivate, organize seating, emphasizing liveliness, cooperation, responsibility, sportifity and accuracy.  Keywords: Two Stay Two Stray, Studies Learning Abstrak: Implementasi Model Kooperatif Tipe Two Stay Twostray Dalam Peningkatan Pembelajaran IPS  Siswa Kelas V SDN3 Krakal Tahun 2013/2014. Tujuan dari penelitian ini adalah untuk mendeskripsikan pelaksanaan model kooperatif Two Stay Two Stray dalam peningkatan pembelajaran IPS dan menemukan kendala serta solusi. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas dan dilaksanakan dalam tiga siklus. Hasil penelitian menunjukkan bahwa: Model Pelaksanaan koperasi Two Stay Two Stray dapat meningkatkan kelas IPS V. Kendalanya yaitu: siswa cerdas lebih aktif dan mendominasi, dan pengaturan tempat duduk kurang. Solusinya adalah: memotivasi, mengatur tempat duduk, menekankan keaktifan, kerjasama, tanggung jawab, sportifitas dan ketepatan. Kata kunci: Two Stay Two Stray, Pembelajaran IPS